Effectiveness of Spotify Podcast-Based Rotating Trio Exchange Learning Model in Indonesian Language Learning for Grade V Students - Maharani, Tiara; Herwani, Suci (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
Speaking skills are one of the language skills that must be mastered by students but some students experience difficulties or obstacles when asked to express opinions or ideas in front of the class. This is motivated by the lack of vocabulary owned by students so that it inhibits students from expressing their ideas. The purpose of this study was to determine the effectiveness of the rotation trio exchange learning model assisted by spotify popcast media in Indonesian language learning to improve speaking skills. The research method used quantitative quasi experimental method through pretest-posttest control group design by applying probability sampling method through random cluster sampling. The results showed that there was a positive influence on the experimental class after being given treatment, based on the independent sample t-test, the Sig value of speaking skills was 0.045, this value was smaller than the alpha value of 0.05. This is reinforced by the results of the analysis of the average value of the experimental class speaking skills pretest value of 55.82 rose to 72.00 on the posttest.  Thus it can be interpreted that the rotation trio exchange learning model assisted by spotify popcast media is effectively used to improve speaking skills.